What makes or mars the facility-based childbirth experience: thematic analysis of women's childbirth experiences in western Kenya - Patience A. Afulani; Leah Kirumbi; Audrey Lyndon (BMC, 2017)
Abstract Background Sub-Saharan Africa accounts for approximately 66% of global maternal deaths. Poor person-centered maternity care, which emphasizes the quality of patient experience, contributes both directly and indirectly to these poor outcomes. Yet, few studies in low resource settings have examined what is important to women during childbirth from their perspective. The aim of this study is to examine women's facility-based childbirth experiences in a rural county in Kenya, to identify aspects of care that contribute to a positive or negative birth experience. Methods Data are from eight focus group discussions conducted in a rural county in western Kenya in October and November 2016, with 58 mothers aged 15 to 49 years who gave birth in the preceding nine weeks. We recorded and transcribed the discussions and used a thematic approach for data analysis. Results The findings suggest four factors influence women's perceptions of quality of care: responsiveness, supportive care, dignified care, and effective communication. Women had a positive experience when they were received well at the health facility, treated with kindness and respect, and given sufficient information about their care. The reverse led to a negative experience. These experiences were influenced by the behavior of both clinical and support staff and the facility environment. Conclusions This study extends the literature on person-centered maternity care in low resource settings. To improve person-centered maternity care, interventions need to address the responsiveness of health facilities, ensure women receive supportive and dignified care, and promote effective patient-provider communication.